Venom Proteome of Spine-Bellied Sea Snake (Hydrophis curtus) from Penang, Malaysia: Toxicity Correlation, Immunoprofiling and Cross-Neutralization by Sea Snake Antivenom - Tan, Choo Hock; Tan, Kae Yi; Ng, Tzu Shan; Sim, Si Mui; Tan, Nget Hong (MDPI, 2018)
The venom proteome of Hydrophis curtus (synonym: Lapemis hardwickii) from Penang, Malaysia was investigated with nano-electrospray ionization-liquid chromatography tandem mass spectrometry (ESI-LCMS/MS) of the reverse-phase high-performance liquid chromatography (HPLC) venom fractions. Thirty distinct protein forms were identified as toxins from ten families. The three major protein families were phospholipase A2 (PLA2, 62.0% of total venom proteins), three-finger toxin (3FTX, 26.33%) and cysteine-rich secretory protein (CRiSP, 9.00%). PLA2 comprises diverse homologues (11 forms), predominantly the acidic subtypes (48.26%). 3FTX composed of one short alpha-neurotoxin (SNTX, 22.89%) and four long alpha-neurotoxins (LNTX, 3.44%). Both SNTX and LNTX were lethal in mice (intravenous LD50 = 0.10 and 0.24 µg/g, respectively) but the PLA2 were non-lethal (LD50 >1 µg/g). The more abundant and toxic SNTX appeared to be the main driver of venom lethality (holovenom LD50 = 0.20 µg/g). The heterologous Sea Snake Antivenom (SSAV, Australia) effectively cross-neutralized the venom (normalized potency = 9.35 mg venom neutralized per g antivenom) and the two neurotoxins in vivo, with the LNTX being neutralized more effectively (normalized potency = 3.5 mg toxin/g antivenom) than SNTX (normalized potency = 1.57 mg/g). SSAV immunorecognition was strong toward PLA2 but moderate-to-weak toward the alpha-neurotoxins, indicating that neutralization of the alpha-neurotoxins should be further improved.